Developing a Comprehensive Information System Architecture Framework to Support Digital Transformation for Small and Medium Enterprises in Vietnam - Nguyen Manh , Tuan; Nguyen Trung , Tuan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
Digital transformation (DT) plays a crucial role in enhancing the competitiveness and operational efficiency of small and medium-sized enterprises (SMEs) in Vietnam. However, this process requires a comprehensive strategy and synchronization between technical and managerial elements, which many SMEs still lack. This study proposes a comprehensive information system architecture framework based on the TOGAF Architecture Framework to support the DT process for SMEs. The designed architecture framework includes five main reference models: Business Reference Model (BRM), Data Reference Model (DRM), Application Reference Model (ARM), Technology Reference Model (TRM), and Security Reference Model (SRM). This framework not only assists SMEs in developing a clear and suitable DT roadmap but also provides the necessary tools to manage and monitor the progress of DT projects, ensuring flexibility and adaptability to market fluctuations.